2020
DOI: 10.1186/s40594-020-00215-6
|View full text |Cite
|
Sign up to set email alerts
|

Factors influencing the academic success of Latinx students matriculating at 2-year and transferring to 4-year US institutions—implications for STEM majors: a systematic review of the literature

Abstract: This systematic review identifies factors that prior studies have identified as supporting the academic success of Latinx transfer students, who matriculate at 2-year institutions with respect to earning a 4-year baccalaureate degree in a STEM field. Since the students matriculate at a 2-year institution, they must, at some point in their academic career, transfer to a 4-year institution to earn the baccalaureate degree. Search and screening procedures identified 59 qualifying studies describing factors suppor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
29
0
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 30 publications
(36 citation statements)
references
References 82 publications
4
29
0
3
Order By: Relevance
“…Social capital provides an assets-based (also called anti-deficit) framing by its focus on the assets present in students' social networks. Our research adds to the growing body of assets-based literature on underrepresented students in STEM (Castro, 2014;Johnson, Brown, Carlone, & Cuevas, 2011;Martin & Garza, 2020;Pawley, 2019;Rahm & Moore, 2016;Syed, Azmitia, & Cooper, 2011;Winterer, Froyd, Borrego, Martin, & Foster, 2020) by highlighting the capital present in their families, and by illustrating how underrepresented students use parental social capital to declare and then persist in undergraduate engineering majors. Following Harper's recommendation to use anti-deficit frameworks to "explore and better understand the enablers of minority student achievement in STEM" (Harper, 2010, p. 64), our work considers this research question: In what ways does social capital provided by parents contribute to White women and women and men underrepresented minority students' decisions to pursue and persist in engineering undergraduate degree programs?…”
Section: Introductionmentioning
confidence: 83%
“…Social capital provides an assets-based (also called anti-deficit) framing by its focus on the assets present in students' social networks. Our research adds to the growing body of assets-based literature on underrepresented students in STEM (Castro, 2014;Johnson, Brown, Carlone, & Cuevas, 2011;Martin & Garza, 2020;Pawley, 2019;Rahm & Moore, 2016;Syed, Azmitia, & Cooper, 2011;Winterer, Froyd, Borrego, Martin, & Foster, 2020) by highlighting the capital present in their families, and by illustrating how underrepresented students use parental social capital to declare and then persist in undergraduate engineering majors. Following Harper's recommendation to use anti-deficit frameworks to "explore and better understand the enablers of minority student achievement in STEM" (Harper, 2010, p. 64), our work considers this research question: In what ways does social capital provided by parents contribute to White women and women and men underrepresented minority students' decisions to pursue and persist in engineering undergraduate degree programs?…”
Section: Introductionmentioning
confidence: 83%
“…A 2007 review of strategies to increase diversity in STEM found that mentoring programs are widely utilized and can lead to higher grade point averages (GPAs), increased self-efficacy, and more clearly defined academic goals (Tsui, 2007 ). A recent review of factors contributing to academic success among Latinx STEM majors similarly identified mentoring, including peer mentoring, as a key driver of success for this population (Winterer et al, 2020 ).…”
Section: Introductionmentioning
confidence: 99%
“…Similarly, we found agreement with Contreras Aguirre et al's (2020) work that found that positive relationships with faculty could similarly support students on their STEM pathway. While prior research studies have indicated the importance of faculty mentoring and contact with instructors (Martin et al, 2019;Winterer et al, 2020) and we found that was an important factor for some of our Fellows, the presence of such a supportive faculty member was inconsistently present for our students and instead they more often relied on families, peers, and the cultural capital (or CCW) they brought with them to succeed.…”
Section: Discussionmentioning
confidence: 55%
“…In a review of 59 studies on what institutional factors could support academic success in Hispanic college students, Winterer et al (2020) found eight factors that influence success, listed in order by those with the greatest number of studies supporting the factors. The factors identified were “peer interactions, cultural climate, advising, coursework articulation, academic integration, support services, asset-based factors, and outreach” (p. 8).…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation